MANAJEMEN BIAYA AKTIVITAS DI-ERA PANDEMI COVID-19 PADA HOME INDUSTRI DI DESA MUARA PENIMBUNG ILIR - Maryati, Sri; Ichsan Siregar, Muhammad; Saggaf, Abdullah; Sartika Pratiwi, Trie; Yusnaini, Yusnaini (Jurnal Abdimas Musi Charitas, 2022)
The COVID-19 virus has had a significant impact on businesses. Both household business actors, small and medium businesses and businesses in an even larger scope. As one of the government's efforts to control the occurrence of a significant impact, the enactment of policies that support business actors to survive and also funding assistance that can be absorbed directlyThis service aims to provide understanding and knowledge as well as related activity cost management to be implemented as a provision in identifying costs attached to products, especially songket products at Songket SMEs in Muara Penimbung Ilir. Sriwijaya University through the service program did not escape participating in efforts to reduce the impact of Covid-19 for business actors by attracting villages in Inderalaya District, especially Muara Penimbung Village which is a fostered village of Sriwijaya University. Muara Penimbung Ilir Village is a village that is familiar with songket craftsmen. This service is carried out using several stages, namely the preparation stage, the core activity stage, and the monitoring and evaluation stage. As for this service activity, it concludes that the diversity of educational backgrounds and community livelihoods is one of the factors that Muara Penimbung Village requires attention in order to survive in the Covid 19 Pandemic Era, especially for Songket business actors. Lack of knowledge related to cost management makes it difficult for business actors to control costs and have not been able to identify costs that have added value and do not have added value for their products and which activity costs are attached to these products so that they are able to contribute to determining the selling price.Based on the results of our dedication in a series of stages, songket business actors have been able to understand and identify value-added and non-value-added costs and have tried to take into account related costs that can be considered to add value to their products.